Comparing Cognitive Behavioral Therapy and Systemic Therapy for Social Anxiety Disorder: Randomized Controlled Pilot Trial (SOPHO‐CBT/ST). Issue 4 (27th October 2019) - Hunger, Christina; Hilzinger, Rebecca; Klewinghaus, Laura; Deusser, Laura; Sander, Anja; Mander, Johannes; Bents, Hinrich; Ditzen, Beate; Schweitzer, Jochen
Abstract : This randomized controlled trial (RCT) aimed to pilot the newly developed manualized and monitored systemic therapy (ST) for social anxiety disorder (SAD), as compared to manualized and monitored cognitive behavioral therapy (CBT). We conducted a prospective multicenter, assessor‐blind pilot RCT on 38 outpatients (ICD F40.1; Structured Clinical Interview for DSM (SCID); Liebowitz Social Anxiety Scale, LSAS‐SR >30). The primary outcome was level of social anxiety (LSAS‐SR) at the end of treatment. A total of 252 persons were screened, and 38 patients were randomized and started therapy (CBT: 20 patients; ST: 18 patients; age: M  =   36 years, SD  = 14). Within‐group, simple‐effect intent‐to‐treat analyses (ITT) showed significant reduction in LSAS‐SR (CBT: d  = 1.04; ST: d  = 1.67), while ITT mixed‐design ANOVA demonstrated the advantage of ST ( d  = 0.81). Per‐protocol analyses supported these results. Remission based on reliable change indices also demonstrated significant difference (LSAS‐SR: 15% in CBT; 39% in ST; h : 0.550), supported by blind diagnosticians' ratings of those who completed therapy (SCID; 45% in CBT, 78% in ST, p  =   .083). No adverse events were reported. CBT and ST both reduced social anxiety, supporting patient improvement with the newly developed ST for SAD; this has yet to be verified in a subsequent confirmatory RCT. Abstract : Este ensayo controlado aleatorizado tuvo como finalidad probar la terapia sistémica (TS) estandarizada y monitoreada recientemente desarrollada para el trastorno de ansiedad social en comparación con la terapia cognitivo‐conductual (TCC) estandarizada y monitoreada. Realizamos un ensayo controlado aleatorizado prospectivo, multicentro y con enmascaramiento para el evaluador en 38 pacientes ambulatorios (CIE F40.1; Entrevista Clínica Estructurada para los trastornos del DSM (SCID); Escala de Ansiedad Social de Liebowitz, LSAS‐SR > 30). El resultado principal fue el nivel de ansiedad social (LSAS‐SR) al final del tratamiento. Se evaluó a un total de 252 personas, 38 pacientes fueron aleatorizados y comenzaron la terapia (TCC: 20 pacientes; TS: 18 pacientes; edad: promedio = 36 años, desviación estándar = 14). Los análisis intragrupales, de efecto simple, con intención de tratar demostraron una reducción significativa del LSAS‐SR (TCC: d = 1.04; TS: d = 1.67), mientras que el análisis de varianza de diseño mixto con intención de tratar demostró la ventaja de la TS ( d = 0.81). Los análisis por protocolo respaldaron estos resultados. La remisión basada en los índices de cambio fiable también demostró una diferencia significativa (LSAS‐SR: 15% en la TCC; 39% en la TS; h : 0.550), respaldada por diferencias casi significativas en las valoraciones con enmascaramiento para los evaluadores de aquellos que completaron la terapia (SCID; 45% en la TCC, 78% en la TS, p = 0.083). No se informaron efectos adversos. Tanto la TCC como la TS reducen la ansiedad social y respaldan la mejora de los pacientes con la terapia sistémica recientemente desarrollada para los trastornos de ansiedad social; esto aun debe verificarse en un ensayo controlado aleatorizado confirmatorio posterior. Abstract : 本研究中的随机控制试验(RCT)是一个对新开发的系统治疗(ST)的初步研究, 该系统治疗是针对社交恐惧症(SAD)的有指导性和监控性的疗法, 文中与之比较的是有指导性和监控性的认知行为疗法(CBT)。我们的研究对象是38个门诊病人(ICD F40.1;对DSM的结构性临床访谈(SCID);列博维茨社交恐惧等级量表, LSAS‐SR在30以上), 他们接受了预期的多中心的, 测评者身份不告知的随机控制实验(RCT)。主要结果查看的是治疗结束后的社交焦虑LSAS‐SR水平。252个人接受筛查, 38个病人被随机安排接受治疗(认知行为疗法CBT: 20 个病人; 系统治疗ST: 18个病人; age: 年龄中位数 M = 36 岁, 标准方差 SD = 14)。在群组内, 目的导向治疗意向性分析表明 LSAS‐SR (CBT: d = 1.04; ST: d = 1.67)有显著性降低, 而ITT混合设计方差分析证明ST的优势( d = 0.81)。符合计划人群分析结果支持了以上结论。基于可信改变指数RCI的变小也证实了显著性差异性(LSAS‐SR: 15% in CBT; 39% in ST; h : 0.550), 这个类似的显著性差异也被那些完成了治疗后的匿名诊断测评的结果支持(SCID; 45% in CBT, 78% in ST, p = 0.083)。尚未出现报告的逆向性的事件。认知行为治疗CBT和系统治疗ST都可以降低社交焦虑, 通过新开发的针对社交恐惧症SAD的系统治疗ST促进了病人的好转 ;但是, 这还需要在接下来的证实性的"随机控制试验" (RCT)中得到进一步证明。